Analysis of the importance of using group work to teach effectively EFL : a study conducted with students of the G.E.B.G. P.C. Pocrí Secundary School Aguadulce, Coclé - Casas R., Lester; Hernández, Patricia de (Santiago, Veraguas : Centro Regional Universitario de Veraguas, 2004)
The effectiveness of group works as instructional technique for teaching English as a foreign language has become eident in recent years as a new technique, it can be used to salve many language learning problems before students progress to hiçiher levels of education. The lack of English knowledge and skills on the part of students of Centro de Enseñanza Básica General secondary schools in Aguadulce has had repercussions after the learners enroll in high school and this largely results from the use of ineffective or inappropriate teaching methods in junior high school (primer ciclo). These students almost always get low grades when they study English in their secondary schools because they were not well prepared. The lack of methodology in some of the professors do not help beginner students of the C.E.B.G. secondary schools to learn the English language efficiently. Too many students working individually is not a good technique to learn a language. Most of the time the learners memorize the material for those moments when they are tested, and when test time has passed, they forget it. The lack of group constructivist activities such as dialogs, role plays, guessing games and so on. Sometime teachers can make classes boring and unnecessarily hard, and students do not have a good instructional aid in English; for example they need a good environment with pictures, cartoons, poems, and so on in English because these things will make them feel that they are n an English atmosphere or "place". The lack of English books in the secondary school libraries is a problem because expensive books are difficult to buy and they are written most of the time for native speakers. In addition, these books do not contain information that is necessary for foreign teachers and students. Professors with old ideas about English techniques can profit from group work as a new technique for English instructions. Most of the time there is too much noise in the classrooms because schools are not appropriately located; there is not air condition and the doors are always open creating a lot of distraction from the outside environment. The classrooms are uncomfortable; there are too many students in a class; and rooms are unattractive without a good decoration to create an environment conducive to learning English.
"Trabajo de graduación presentado para optar por el título de Licenciado en Humanidades con especialización en Inglés". -- Página de título.
Keywords: INGLES -- ENSEÑANZA SECUNDARIA -- METODOLOGIA -- PANAMA -- COCLE (PROVINCIA); TRABAJO EN GRUPOS (EDUCACION) -- ENSEÑANZA -- PANAMA -- COCLE (PROVINCIA); ACTIVIDADES CREATIVAS Y TRABAJO DE CLASE -- ENSEÑANZA -- PANAMA -- COCLE (PROVINCIA); ESTUDIANTES DE EDUCACION MEDIA -- ACTITUDES -- PANAMA -- COCLE (PROVINCIA); TECNICAS DE ENSEÑANZA -- PANAMA; ESTRATEGIAS DE APRENDIZAJE -- PANAMA; INGLES -- TESIS Y DISERTACIONES ACADEMICAS